2002
DOI: 10.1182/blood.v99.8.2913
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus inhibits maturation and impairs function of monocyte-derived dendritic cells

Abstract: Whereas virus infections in general stimulate DC maturation and lead to the generation of efficient antiviral T-cell responses, some viruses have developed mechanisms to interfere with the normal functions of DCs. Human immunodeficiency virus (HIV), measles virus, herpes simplex virus-1 (HSV-1), and vaccinia virus, for example, are all known to cause defects in DC maturation and function which consequently lead to impaired antiviral T-cell responses. [1][2][3][4] The major risk factor for HCMV infection in bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
208
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(222 citation statements)
references
References 51 publications
12
208
2
Order By: Relevance
“…It was previously reported that clinical HCMV isolates (in contrast to laboratory strains and HELF-adapted clinical isolates) are able to infect DC [21]. HCMV infection has been reported to inhibit DC maturation as shown by down-regulation of surface MHC and costimulatory molecule expression [22]. In our study, we found that two molecules highly expressed in the mature pheno- type (MHC class I and CD40) were partially downregulated in HCMV-infected DC, and HLA-DR was only partially up-regulated, while CD83 was not expressed.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that clinical HCMV isolates (in contrast to laboratory strains and HELF-adapted clinical isolates) are able to infect DC [21]. HCMV infection has been reported to inhibit DC maturation as shown by down-regulation of surface MHC and costimulatory molecule expression [22]. In our study, we found that two molecules highly expressed in the mature pheno- type (MHC class I and CD40) were partially downregulated in HCMV-infected DC, and HLA-DR was only partially up-regulated, while CD83 was not expressed.…”
Section: Discussionmentioning
confidence: 99%
“…These include the US2 and US3, which have been shown to directly interfere with class II MHC Ag presentation (46,47), and a viral orthologue of IL-10 that has similar immunosuppressive properties as human 45). CMV can also directly infect human myeloid dendritic cells (48,49), which are key APCs for the initiation of the adaptive immune response and in directing CD4 ϩ T cell differentiation toward Th1 effector function or other fates (50). Such infection may interfere with the ability of dendritic cells to present Ags to CD4 ϩ T cells (48) and produce IL-12 (49), a key cytokine for the generation of Th1 cells in humans (25).…”
Section: Discussionmentioning
confidence: 99%
“…22 In addition, the virus also encodes proteins that act as receptors for host inflammatory cytokines, thereby reducing localized cytokine effectiveness by acting as cytokine sinks. 6 Similarly, a number of HCMV encoded genes known to be expressed during lytic infection can interfere with both MHC Class I and II restricted antigen processing and presentation, thereby robustly inhibiting CD4 1 and CD8 1 T-cell recognition 4,23 as well as costimulatory T-cell signalling 24 (Figure 3). On the one hand then, HCMV expresses multiple immunevasins which are known to work potently in vitro but, even in the face of these, host immune response are still able to resolve primary HCMV infection.…”
Section: Primary Infection and The Immune Response To Virus In Lytic mentioning
confidence: 99%